Administration of granulocyte-macrophage colony-stimulating factor enhanced chimeric antigen receptor T-cell expansion and cellular immunity recovery without inducing cytokine release syndrome - Jiang, Ying; Feng, Dan; Wang, Chun; Zhang, Yanlei; Zhao, Chuxian; Li, Su; Qin, Youwen; Chang, Alex H.; Zhu, Jun (Frontiers in Medicine, 2022)
Background: Neutropenia and cytokine release syndrome (CRS) are two major toxicities of CAR-T cell therapy. GM-CSF is an ideal candidate treatment for neutropenia except for its potential aggravation of CRS. We hypothesized that the optimal timing of supplemental with GM-CSF in a shortage of host immunity and CAR T-cell was chosen as avoidance of CRS. In the study we evaluated the safety and efficacy of GM-CSF intervention post-CAR T-cell therapy while circulating CAR T-cell declined. Methods: Nine patients received GM-CSF therapy who displayed moderate neutropenia with absolute neutrophil counts (ANC) <1500 cells/mm3 with concomitant declination of circulating CAR T-cell. Results: The median duration of GM-CSF intervention was 15 days (4-30). CAR T-cell expansion was observed in peripheral blood (PB) of seven patients (7/9). The median baseline and peak CAR T cells count in PB of the seven patients with CAR T-cell expansion were 0.85×106/L (0-50.9) and 6.06×106/L (1.43-112.55). And the peaks of CAR T-cell levels in PB appeared in day 7 (2-11) following the initiation of GM-CSF administration with increases of 2.84×106/L (0.38-61.65). Also, increased white blood cells in PB was observed in all patients. The median onset and duration time of WBC recovery were 9 (1-14) and 17(3-53) days. Moreover, the increment of WBC, neutrophil, lymphocyte and CD3-CD16+CD56+ natural killer cell in PB was observed. In addition, no CRS or fatal infection occurred during GM-CSF treatment. Conclusion: This study provides evidence for the clinical feasibility of combining CAR T-cell therapy with the GM-CSF to treat neutropenia patients with concomitant declination of circulating CAR T-cell.